Construction Management Performance Analysis of Dittopad Flat Building Project - Muhammad Rijali Sukur Pelu; Adden Trianto; Samudra; Okri Asfino Putra; Muhammad Bagus Yulistian; Oktavianus Pranoto; Rakyan Choiruna Daffarel; Rena Avinika Ningtyas; Yuliza Putri Rahmayeni; Dewi Fauzah (Potensi: Jurnal Sipil Politeknik, 2024)
In construction work, construction management is needed. Construction management is the activity of planning, actuating and controlling projects using resources effectively and efficiently. The fundamental functions of construction management are planning, organizing, actuating and controlling. The Dittopad flats are a construction carried out by Pusziad TNI AD to raise personnel morale by providing a place to live. The purpose of writing is to analyze the application of construction management that occurred in the Dittopad Flats building construction project. The research method used was a literature review obtained by filling out a questionnaire with 50 respondents involved in the construction of the Dittopad Flats. The analysis was carried out using factors that influence the construction work system on basic management functions related to aspects of time, cost and quality. Based on factor analysis of the construction management work system, it was found that the most influencing function was planning with a value of 4.31. From the analysis of the actions taken by construction management at the Dittopad Flats, it was found that the one that had the most influence was the planning stage with a value of 4.26.